Acute encephalitis as initial presentation of leptospirosis - Puca, Edmond; Majko, Joana; Puca, Entela; Qyra, Elda; Gega, Arjet; Pipero, Pellumb (The Journal of Infection in Developing Countries, 2017)
Encephalitis is an acute inflammation of the brain matter, very often associated with viral infections, but it can also be caused by non-viral pathogens such as leptospirosis. Leptospirosis is a systemic disease caused by bacteria of the Leptospira genus. Leptospiral infection has a broad spectrum of clinical manifestations ranging from subclinical or mild illness to a fulminant life-threatening illness. In this case report we describe a young patient from Southern Albania with isolated encephalitis caused by Leptospira, where acute encephalitis was the initial presentation of the disease.